Serodiagnosis in plant pathology: Present status and future prospects - H.Dar,N.A.Bhat,A.Anwar,H.Ashraf,S.Akhtar, M.R.Mir,R.Rashid,S.H.Wani,J.A.Bhat,M.Habib,N.Wan, K.A.Bhat,M.A.Bhat,S.D.Masoodi,M.Ahmad,G. (Journal of Ecobiotechnology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: Garamond; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold; mso-bidi-font-style: italic;">When any foreign protein (antigen) such as virus, fungi or a bacterial protein is injected into a mammal or a bird, it induces the animal to produce specific proteins called antibodies. After their production antibodies react specifically to the portion of the pathogen called as antigenic determinant. From diverse population of antibodies found in sera of immunized animals, monoclonal antibodies (MAbs) consist of homogeneous antibody molecules. MAbs have the same specificity and affinity for an antigenic determinant. They have been widely applied in the areas of medical, veterinary and agricultural sciences as they confer the advantage of defined specificity and quick availability of unlimited quantities. The production of MAbs is possible through hybridoma technology. MAbs have now been developed that are specific for genus, species and isolates of plant pathogenic viruses, bacteria, fungi, mycoplasma like organism (MLOs) and nematodes. MAbs are used in detection and quantification of pathogens. In serological testing the pathogen and its antibody are brought in contact in several ways such as ring interface test, micro precipitin test, diffusion test, enzyme linked immunosorbent assay (ELISA), immunosorbent electron microscopy and immunofluorescent staining. Serology also helps to understand antigenic structure of viruses, characterization of function of particle proteins that facilitate recognition by the vector and serological relationship among viruses. New ways to produce antibodies that have been developed using DNA-technology also called as recombinant antibodies are discussed in detail.<span style="font-size: 10.5pt; color: black; line-height: 110%; font-family: ";Times New Roman";; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-size: 10.0pt;">Ã‚Â Ã‚Â Ã‚Â